Social determinants of health: trigger for the LGBTIA+ population inclusion in health services? - Londero, Carolina Araujo; de Souza, Andreza Cossettin; Colomé, Juliana Silveira; de Souza, Martha Helena Teixeira; Zamberlan, Claudia (Disciplinarum Scientia | Saúde, 2023)
Objective: To understand the scientific evidence about the social determinants of health as triggers for the inclusion of the LGBTIA+ population in health services. Method: Systematic review of the literature, presenting a meta-synthesis as a review protocol. It was based on a research question in accordance with the PICO strategy, namely: Are the Social Determinants of Health triggering elements for the inclusion of the LGBTIA+ population in health services?. The data collection process took place from December 2021 to March 2022. The search for studies took place in the following databases: Medical Literature Analysis and Retrieval System Online, Latin American and Caribbean Literature in Health Sciences and Scientific Electronic Library Online. Data analysis was qualitative. Results: Two categories emerged: The consolidation of affirmative policies for the LGBTIA+ population and, DSS and the LGBTIA+ population, which demonstrated how public policies link care to this population as well as the interaction of these policies with the social determinants of health. Conclusion: It is clear that the LGBTIA+ population is included in the social determinants of health, however there is much progress to be made towards full access to health goods and services